ARTISTIC INDIVIDUALITY OF D. RUBINA'S STORIES "AT A LONG TRAFFIC LIGHT", "TASPESTRY", "SCARF" (World Economics and Finance Bulletin, 2022)
The article deals with the artistic originality of Dina Rubina's stories "At a Long Traffic Light", "Tapestry", "Scarf". A special place in the article is given to compositional features, sound painting, coloring, odorism, landscape sketches, symbolism, the objective world, the poetics of sensory elements in the analyzed stories.
Keywords: Composition; sound painting; coloring; symbolism